Efficient identification of Malassezia yeasts by matrix‐assisted laser desorption ionization‐time of flight mass spectrometry (MALDI‐TOF MS). (18th February 2014) - Kolecka, A.; Khayhan, K.; Arabatzis, M.; Velegraki, A.; Kostrzewa, M.; Andersson, A.; Scheynius, A.; Cafarchia, C.; Iatta, R.; Montagna, M.T.; Youngchim, S.; Cabañes, F.J.; et al.
Abstract : What's already known about this topic? Matrix‐assisted laser desorption ionization‐time of flight mass spectrometry (MALDI‐TOF MS) has been developed for the rapid identification of microorganisms and proved to be a robust tool for the recognition of bacterial species. Recently, it was shown that MALDI‐TOF MS provided reliable identification of yeasts and filamentous fungi. Identification of Malassezia isolates by routine methods remains laborious and results in a relatively high number of erroneous results. What does this study add? A database of reference mass spectra resulting in efficient and correct identification of all Malassezia species by MALDI‐TOF MS in a short turnaround time. MALDI‐TOF MS results were consistent with those obtained by sequence analyses. The method may efficiently demonstrate the involvement of different Malassezia species in skin diseases. Application of MALDI‐TOF MS for the identification of Malassezia isolates is of clinical importance as fast and reliable identification will result in early treatment. Summary: Background: Infections caused by Malassezia yeasts are most likely underdiagnosed, because fatty acid supplementation is needed for growth. Rapid identification of Malassezia species is essential for appropriate treatment of Malassezia ‐related skin infections, fungaemia and nosocomial outbreaks in neonates, children and adults and can be life‐saving for those patients. Ma‐assisted laser desorption ionization‐time of flight mass spectrometry (MALDI‐TOF MS) has been reported to be a rapid and reliable diagnostic tool to identify clinically important yeasts, but so far no data have been reported on identification of Malassezia isolates with this technique. Objectives: To create an extensive database of main mass spectra (MSPs) that will allow quick identification of Malassezia species by MALDI‐TOF MS. Methods: An in‐house library of 113 MSPs was created from 48 reference strains from the CBS‐KNAW yeast collection. The in‐house library was challenged with two test sets of Malassezia strains, namely 165 reference strains from the CBS collection and 338 isolates collected in Greece, Italy, Sweden and Thailand. Results: MALDI‐TOF MS allowed correct identification of all 14 Malassezia spp. MALDI‐TOF MS results were concordant with those of sequence analyses of the internal transcribed spacers (ITS1/ITS2) and the D1/D2 domains of the large subunit of the ribosomal DNA. Conclusions: Implementation of the MALDI‐TOF MS system as a routine identification tool will contribute to correct identification of Malassezia yeasts with minimal effort and in a short turnaround time, which is especially important for the rapid identification of Malassezia in skin diseases and nosocomial outbreaks.